2014
DOI: 10.5539/ep.v3n3p38
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Heavy Metals and Hydrocarbons in Hemichromis Fasciatus Exposed to Surface Water in Borrow Pits Located Within Onshore Oil Exploration and Production Area

Abstract: A field bioaccumulation study was carried out. Juvenile hemichromis fasciatus in net cages were exposed to contaminated surface water in borrow pits located within oil exploration and production (E & P) installations within the Niger Delta region of Nigeria during wet and dry seasons.Percentage mortality ranged between 2% and 3.8%. Assuming a first order kinetics and steady state at day 14; toxicokinetic variables were obtained for xenobiotics assessed. The up-take rate constant k, ranged from 38.47 Hemichromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…This may be due to run-off, tidal incursions and flooding. This corroborates with the research undertaken by Vaikosen et al [18], who reported a higher value in wet season than the dry season. The finding in this study is consistent with the result of other studies [19,20].…”
Section: Sedimentsupporting
confidence: 93%
“…This may be due to run-off, tidal incursions and flooding. This corroborates with the research undertaken by Vaikosen et al [18], who reported a higher value in wet season than the dry season. The finding in this study is consistent with the result of other studies [19,20].…”
Section: Sedimentsupporting
confidence: 93%
“…Oil spillage and petroleum products are anthropogenic sources of PAHs in the environment 11. Organic pollutants such as PAHs have a tendency to accumulate in biota and undergo food chain magnification 12. The Atlas Cove jetty, which serves as a major storage depot for imported petrol before distribution, increases the possibility of contamination during the offloading process from vessels into the Atlas Cove product storage tank.…”
Section: Introductionmentioning
confidence: 99%
“…The modified method by Adewuyi et al [19]; [20] was used for sample digestion.The samples were grinded using an acid (3m nitric acid) prewashed mortar and pestle, sieved into a well labeled transparent plastic containers by passing them through 1mm mesh, 1g of each of the sieved samples were accurately weighed into different digestion flask, well clamp to a retort stand. 10ml of ratio 10:1 mixture or Nitric (HNO3) and perchloric (HCIO4) acid were added to the sample in each of the clamped digestion flask, swirled and allowed for some minutes for any reaction to subside.…”
Section: Determination Of Heavy Metalsmentioning
confidence: 99%